Eptesicus nilssoni - Karl F. Koopman (Smithsonian Institution Press, 1993)
Eptesicus nilssoni (Keyserling and Blasius, 1839). Arch. Naturgesch., 5(1):315. TYPE LOCALITY: Sweden. DISTRIBUTION: W and E Europe to E Siberia and NW China; north beyond Arctic Circle in Scandinavia, south to Bulgaria, Iraq, the Elburz Mtns (N Iran), The Pamirs and W China (not Tibet); Nepal; Honshu, Hokkaido (Japan); Sakhalin Isl (Russia). SYNONYMS: atratus, centralasiaticus, gobiensis, japonensis, kashgaricus, parvus, propinquus. COMMENTS: Subgenus Eptesicus. Includes propinquus; see W. B. Davis (1965:230). Includes japonensis; see Corbet (1978c:57), but also see Yoshiyuki (1989). Includes gobiensis; see Corbet (1978c); but see also Strelkov (1986), who discussed status, relations, and distribution, and Pavlinov and Rossolimo (1987). Revised by Wallin (1969). Published as part of Karl F. Koopman, 1993, Order Chiroptera, pp. 137-241 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 202, DOI: 10.5281/zenodo.7353060